Enterprise Risk Management: Improving Embedded Risk Management and Risk Governance - Werner Gleißner; Thomas B. Berger (Risks)
We argue for an integrated, decision-oriented enterprise risk management (ERM) system focused on value drivers rather than risk minimization and using quantitative risk aggregation based on the best available information. Our holistic view on ERM includes cultural, organizational, and technical aspects, presenting seven areas for more effective risk governance and resilience grounded in a robust enterprise framework. Our analysis, supported by a structured literature review, covers these seven key areas for ERM development. Our review shows that risk aggregation, quantification, and decision-making support are only covered by a few publications. The paper offers insights on linking risk management with strategic decision-making using risk aggregation techniques (Monte Carlo simulation).